2006
DOI: 10.1111/j.1440-1754.2006.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous fat necrosis of the newborn: Be aware of hypercalcaemia

Abstract: Subcutaneous fat necrosis of the newborn is an uncommon, self-limiting panniculitis that usually occurs in full-term infants as a consequence of perinatal asphyxia. The cutaneous involvement may be associated with metabolic complications such as hypoglycaemia, thrombocytopenia, hypertriglyceridemia, anemia and hypercalcaemia. The delayed onset of hypercalcaemia, 1-6 months after the development of the skin manifestations, imposes a prolonged follow-up to avoid its acute toxic effects on cardiovascular and rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 14 publications
0
28
0
4
Order By: Relevance
“…Varan et al suggested that severe anaemia in the neonatal period may trigger subcutaneous fat necrosis by reduced tissue perfusion with relative hypoxia and hypothermia [13]. Hypertryglyceridemia has been described in three cases [3,12,14]. It has been documented just before or during the appearance of the cutaneous lesions suggesting a possible mobilisation of fatty acids from affected adipocytes.…”
Section: Discussionmentioning
confidence: 95%
“…Varan et al suggested that severe anaemia in the neonatal period may trigger subcutaneous fat necrosis by reduced tissue perfusion with relative hypoxia and hypothermia [13]. Hypertryglyceridemia has been described in three cases [3,12,14]. It has been documented just before or during the appearance of the cutaneous lesions suggesting a possible mobilisation of fatty acids from affected adipocytes.…”
Section: Discussionmentioning
confidence: 95%
“…The prognosis of the disease is generally good, but it can be complicated by potentially life‐threatening metabolic alterations. Hypercalcaemia is the most dangerous complication of ScFN, and must be treated adequately and quickly …”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcaemia is the most dangerous complication of ScFN, and must be treated adequately and quickly. 10,12,14,16,18,19 To date, and to the best of our knowledge, no case of surgical management for therapeutic purposes has been reported, with the exception of ulcerated lesions. 13,20 No author has ever addressed the issue of lack of regression of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Furosemide may be helpful to induce calciuresis, but has to be used carefully in order to avoid dehydration and consequent worsening of hypercalcemia. Corticosteroids, calcitonin, citrate and bisphosphonates may be required as second-line therapy in resistant cases (10,15). Hypertriglyceridemia and anemia may also occur, as well as thrombocytopenia and hypoglycemia (8,10,14).…”
Section: Discussionmentioning
confidence: 99%